FORMALIZATION OF THE PROBLEM OF SELECTION OF AUTOMATED SYSTEM - A. V. Petukhov (Системный анализ и прикладная информатика)
The results of many years of research in the field of formalizing the task of selecting automated systems for various areas of design and office activities are given. The purpose of the study is the development of methods for qualitative and quantitative evaluation when choosing an automated system, taking into accounts the operating conditions and customer requirements. Qualitative assessment is based on the theory of choice and decision making, which examines the mathematical models of this type of activity. In view of the fact that in the problem under consideration, many alternatives, which are automated systems, are known, it can be related to the choice problem. The peculiarity of this approach is that it does not require a complete restoration of the principle of optimality, but allows us to confine ourselves to information sufficient to identify the optimal variant. The quantitative assessment is based on the determination of the projected annual economic effect from the introduction of an automated system. The described technique can be used by enterprises and organizations in the evaluation of automated systems at the stage preceding the tender for their purchase.